Effect of Fabrication Techniques on the Properties of Fluorohydroxyapatite Scaffolds: A Comparative Study of Freeze-Drying, Solvent Casting, and 3D Printing - Agsous, Maissa; Khireddine, Hafit; Yala, Sabeha; Ustundag, Cem Bulent (WILEY, 2026)
Bone tissue engineering (BTE) aims to address the complex challenge of regenerating critical-size bone defects, where conventional healing is insufficient. This work compares the morphological characteristics of FHA-based scaffolds fabricated via three different methods: solvent casting with particle leaching, freeze-drying, and 3D printing. Each technique demonstrated unique advantages: solvent casting with salt leaching produced interconnected microporous scaffolds (0.5-2 mu m), suitable for cell migration and nutrient diffusion, but with limited control over global geometry. Freeze-drying generated slightly larger pores (2-4 mu m) through ice crystal sublimation, offering improved porosity and surface area while preserving the material's composition. In contrast, 3D printing enabled precise architectural control, yielding scaffolds with dual-scale porosity-micropores (similar to 35 mu m) and macropores (similar to 2000 mu m)-that enhance cell infiltration, vascularization, and osteointegration. The experimental results confirmed initial hypotheses regarding each fabrication method's influence on scaffold morphology. While traditional methods like salt leaching and freeze-drying effectively generate functional porosity, 3D printing stands out for its reproducibility, design versatility, and potential for drug incorporation and controlled release. Therefore, 3D printing was selected as the most suitable platform for the continuation of this study, particularly for advanced applications in tissue engineering and bone regeneration.
Keywords: 3D printing; fluorohydroxyapatite; freeze-drying; scaffolds; sol-gel; solvent casting; HYDROXYAPATITE SCAFFOLDS; MECHANICAL-PROPERTIES; POROUS CERAMICS; PORE STRUCTURE; BONE; FLUORINE; POROSITY; POROGEN; SIZE; Polymer Science